Pemakaian Bahasa Dalam Karya Ilmiah Populer - I Dewa Putu Wijana (JURNAL ARBITRER, 2013)
This article is intended to describe the characteristics of language used in popular scientific discourse, and its differences from ones usually found in pure scientific articles. A close and careful examination through some amount of data extracted from Intisari, one of the most popular scientific megazines in Indonesia, shows that the use of language in the popular megazine is considerably different from those generally exploited in more serious scientific articles. The differences include the use of long and short sentence combinations, reported speech, pronouns, simele and metaphor, diction, conjuction and other syntactic constituent ellipsis, and anecdotes and play on word. The popular style is important to master, especially by anyone who are involved and interested in popular writing activities. Accordingly, the standard variation is not the only style to teach in langage learning.